2016
DOI: 10.1089/thy.2015.0448
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Nutritional Status in Schoolchildren from Public Schools in Brazil: A Cross-Sectional Study Exposes Association with Socioeconomic Factors and Food Insecurity

Abstract: A significant proportion of schoolchildren still have ID or EII in the northeast region of Brazil, emphasizing the importance of committed public policies to address this problem. Socioeconomic factors and the lack of education about nutritional importance of iodine were important influencing factors in the presence of ID in schoolchildren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 30 publications
0
9
1
2
Order By: Relevance
“…Several reports described iodine-deficient pregnant women even in iodine-sufficient areas, despite the existence of an iodization programme, and pregnant women are considered a risk group ( 3 , 12 ). In Brazil, the salt iodization programme is successful at combating iodine deficiency, but ongoing monitoring is mandatory as Brazil is a continental country with vulnerable regions, such as rural areas and lower economic conditions ( 11 ). Recently, the Brazilian government’s salt iodization programme reduced the iodine concentration in salt from 40–60 mg/kg to 15–45 mg/kg based on previous reports pointing to excessive iodine intake ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports described iodine-deficient pregnant women even in iodine-sufficient areas, despite the existence of an iodization programme, and pregnant women are considered a risk group ( 3 , 12 ). In Brazil, the salt iodization programme is successful at combating iodine deficiency, but ongoing monitoring is mandatory as Brazil is a continental country with vulnerable regions, such as rural areas and lower economic conditions ( 11 ). Recently, the Brazilian government’s salt iodization programme reduced the iodine concentration in salt from 40–60 mg/kg to 15–45 mg/kg based on previous reports pointing to excessive iodine intake ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the median UIC is a well-known indicator of iodine intake for the population, individual intakes are highly variable, and a low UIC on any given day might be found despite adequate daily intakes to maintain thyroidal iodine stores ( 21 ). Our study did not evaluate the socioeconomic and educational statuses that are associated with iodine deficiency ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2009 survey, Erdoğan et al ( 6 ) found a significant difference among rural and urban areas in Turkey. There are many studies highlighting the difference in prevalence of ID levels in rural areas ( 18 , 19 ). Therefore, it should be noted that this study does not reflect iodine status of rural populations in Antalya.…”
Section: Discussionmentioning
confidence: 99%
“…Sebagian besar anak yang mengonsumsi garam > 30 ppm berisiko mengalami kelebihan iodium. Hal ini didukung penelitian lain pada anak usia sekolah di Brazil yang menyebutkan anak yang kelebihan iodium diindikasikan akibat kelebihan asupan pangan sumber iodium (Campos et al, 2016). Intervensi pada anak sekolah di Semarang dan Magelang menunjukkan peningkatan status iodium menjadi kelebihan pada kelompok di daerah endemik ringan diduga akibat konsumsi sumber iodium lain selain perlakuan peneliti (Samsudin, Kusumawardani, & Prihatmi, 2015).…”
Section: Hubungan Kadar Iodium Garam Dengan Status Iodium Anakunclassified